Family Businesses and Succession Planning: An Analytical Approach - Adnan Hasan (Vifada Management and Digital Business, 2024)
This study explores the complex interplay of psychological, emotional, and cultural factors in succession planning within family businesses, aiming to provide insights and strategies for effective leadership transitions. The research employs a mixed-methods approach, integrating qualitative interviews with family business leaders and quantitative surveys of 300 family businesses. This design allows for a comprehensive analysis of the determinants of successful succession planning. The findings highlight the critical roles of psychological readiness and emotional commitment in succession processes. Leaders' willingness to relinquish control and successors' emotional investment were pivotal for smooth transitions. Cultural differences also significantly influenced succession practices, with Western businesses favoring formalized, merit-based approaches and Eastern businesses emphasizing family harmony. The study underscores the importance of continuous succession planning and inclusive decision-making processes. The study's insights inform practical strategies for family business owners, advisors, and policymakers. Emphasizing early involvement and mentorship, culturally sensitive practices, and continuous planning can enhance the effectiveness of succession planning, ensuring the long-term sustainability of family businesses.